Prioritizing the pipeline maintenance approach using Analytical Hierarchical Process - Shafiq, N. (Praise Worthy Prize, 2010)
There are a number of cases reported for pipeline failures both in onshore and offshore situation. In order to minimize such failure, there is a need to clearly understand the failure mechanisms, governing factors and further analysis of data can determine the cause and extent of failure. In this study Analytical Hierarchy Process (AHP) was used to determine the risk factor for pipeline failure of the chosen system. AHP provides the multiple criteria scoring results based on expert judgement for prioritizing the pipeline maintenance strategy. For this case study two pipelines networks administered by two different operators, the first one in Malaysia and the other one in Indonesia were chosen. From the analysis of the data obtained by interviewing the pipeline engineers from Malaysia operator, it was obtained that highest risk factor i.e. 41.7% for pipeline failure involved internal corrosion; the other factors in descending order are internal erosion, external impacts, external corrosion, free span and on-bottom stability. From the analysis of Indonesian pipeline, failure due to system operation involved the highest risk factor i.e. 34.7%; other factors are design index, maintenance, and third party index.